DescriptionOf The Quality Of Inpatient Services Based On The Barber Johnson Indicator At Pertamina Cirebon Hospital - Putri Dewi Nalendra Sari; Yani Kamasturyani; Tuti Herawati (Jurnal Kesehatan Mahardika, 2020)
One of the qualities in health care facilities is inpatient services in the availability of a number of beds. The use of beds for inpatient services was assessed through indicators such as BOR, LOS, TOI, and BTO. The purpose of this study was to determine the description of the quality of inpatient services based on Barber Johnson indicators at Pertamina Cirebon Hospital.The research method used is quantitative descriptive. The sample used in this study are inpatient daily census recapitulation data for each room in January - March 2019 total 8 room. The variabel this study is the quality of inpatient servicesbased on the Barber Johnson indicator which includes BOR, LOS, TOI, and BTO with a checklist instrument and analyzed descriptively.The results of this study the rooms included in the Barber Johnson graphic efficiency values in January 2019 of the Tulip and Sakura rooms, in February of Tulip, Flamboyan, and Sakura rooms and in March of VIP, Tulip, and Flamboyan rooms.